Women's Reasons for Attrition from a Nurse Home Visiting Program. Issue 1 (19th December 2013) - Holland, Margaret L.; Christensen, Julie J.; Shone, Laura P.; Kearney, Margaret H.; Kitzman, Harriet J.
ABSTRACT Objective To describe mothers' reasons for leaving a home visiting program early. Design Qualitative descriptive study using semistructured interviews of mothers who dropped out of the Nurse‐Family Partnership (NFP) and two focus groups with nurses and nurse supervisors at an NFP site. Setting A New York State site of a NFP home visitation program for low‐income new mothers designed to improve the physical and emotional care of children. Participants Participants included 21 mothers, 8 nurses, and 3 nurse‐supervisors. Methods Semistructured interviews and focus groups were used to collect data, which were analyzed using content analysis. Results The program was not perceived to fit a mother's needs when she was overwhelmed with other responsibilities, the nurse did not meet her expectations, the content was not of interest, or the mother did not desire visits after the infant was born. Nurses and mothers described the need for mothers to have organizational and communication skills, such as keeping track of appointments, calling to reschedule, articulating needs, and asking for assistance. Disruptive external influences included nurse turnover and unstable living situations, including frequent moves and crowded housing. Each of these types of barriers had potential to interact with the others, creating complex combinations of challenges to retention. Conclusion NFP retention might be improved by reframing program relevance to individual mothers and increasing maternal organizational and communication skill development.